# this is math spec , so hard , i need help , and i will review

Images:
This image has been Flagged as inappropriate Click to unflag
Image (1 of 3)
This image has been Flagged as inappropriate Click to unflag
Image (2 of 3)
This image has been Flagged as inappropriate Click to unflag
Image (3 of 3)
Borys Shumyatskiy | Certified Educator

a. Denote (ax)/(x^2+b) = g(x), then h(x) = arcsin(g(x)).

We know that (arcsinx)' = 1/sqrt(1-x^2). So by the formula for the derivative of the composition

h'(x) = g'(x)/sqrt[1-(g(x))^2] =

[a*(x^2+b - 2x^2)/(x^2+b)^2] / [sqrt(((x^2+b)^2-a^2x^2)/(x^2+b)^2)] =

[a*(b-x^2)/(x^2+b)^2] / [sqrt((x^2+b)^2-a^2x^2) / |x^2+b|] =

a*(b-x^2)/sqrt((x^2+b)^2-a^2x^2) * (1/|x^2+b|).

Here we used that sqrt(u^2) = |u| and that |u|/u^2 = 1/|u|.
So the derivative really has a form we had to prove.

b. (x^2+b)^2 - a^2x^2 = (x^2)^2 - 2x^2*(a^2/2 - b) + b^2.
If (a^2/2 - b) = b this expression becames the full square,
(x^2 - b)^2 and sqrt of it is equal to |b - x^2|.

(a^2/2 - b) = b means that a^2 = 4b and a^2/b = 4. So b=a^2/4>=0
(if b=0 then a=0 and h(x)=0 for all x, so we can consider only b>0).

Then h'(x) = [a/|x^2+b|]*[(b-x^2)/|b-x^2|]. The second multiplier is +-1,
let's consider where + and where -.  b>0 so |x^2+b| = x^2+b.

b-x^2 < 0 when -sqrt(b) < x < sqrt(b) or -a/2 < x < a/2.
At this segment h'(x) = -a/(x^2+b).
For x outside of this segment h'(x) = a/(x^2+b).

h'(x) = a/(x^2+b) when x in (-∞, -sqrt(b)) U (sqrt(b), +∞)
h'(x) = -a/(x^2+b) when x in (-sqrt(b), sqrt(b)).

3. We have to prove that |g(x)| <= 1 for arcsin to have sense.
For a=0 it is trivial and for a>0 b>0. And b=a^2/4.

Consider 1-|g(x)| = (x^2+b-|ax|)/(x^2+b) =

[|x|^2 - 2(|a|/2)|x| + (|a|/2)^2]/(x^2+b).

The denominator >0 for all x and the numerator is equal to
(|x| - |a|/2)^2 >= 0 for all x.

So we proved that 1-|g(x)| >= 0 for all x or |g(x)| <= 1.